Evaluation of scientific and technological innovation efficiency at Shandong Vocational and Technical University of international studies: A two-stage DEA model approach - Jun Zeng; Tao Sun; Li Zhang (PLoS ONE, 2025)
Vocational undergraduate education is an important part of the higher education system, and science and technology innovation is a major function of vocational undergraduate education. Based on the theory of innovation value chain, the scientific and technological innovation activities of colleges and universities can be divided into two stages: knowledge innovation and results transformation. In this paper, we built the shared-input-type correlation DEA (Data envelopment analysis) model of additional inputs, measured the basic data of Shandong Vocational and Technical University of International Studies during the period of 2013–2022 after its schooling went into a formalized way, and estimated the trend information of the scientific and technological research efficiency of Shandong Vocational and Technical University of International Studies based on the comprehensive consideration of the intermediate output reinvestment, the distribution of initial inputs in the sub-stage and the new inputs in the second stage. Our key findings are: the scientific research input-output efficiency of Shandong Vocational and Technical University of International Studies shows a rapid growth trend, from 0.6194 in 2013 to 0.9091 in 2022, and its scientific research efficiency growth rate has increased by 46.77%, with an average annual growth rate of 4.68%. This increase in research efficiency is crucial, as it enhances the institution’s ability to contribute to regional economic development, improves research productivity, and strengthens its role in advancing vocational education. On this basis, we propose targeted policy recommendations, including increasing funding allocation for R&D activities, improving resource utilization efficiency, introducing high-level research talents, and enhancing the alignment between research outputs and industry needs through curriculum adjustments and stronger university-industry collaboration.